The Biography of Col. J.A. Olubobokun a Foremost Nigerian Military Musician - Olatunji, M.O. (Journal of Performing Arts, 2010)
This paper portrays Colonel Josef Adeboyejo Olubobokun (rtd.) as a foremost Nigerian Military musician. It also beams a searchlight into his family and educational background, as well as his contributions and achievements in the area of military music in Nigeria. The field aspect of this research was conducted through interviews with Olubobokun himself and other serving and retired band officers in the Nigerian armed forces and the Police. In addition, scores of some of his military band instrumental and vocal music were collected, categorized and analyzed in order to expound to what extent these have conformed to the musician's assertions - especially in the area of indigenization of military music in Nigeria. It was revealed, among other things, that Col. J.A. Olubobokun (rtd.) was the first Nigerian to be commissioned in the Nigerian Army Band Corps. This also made him become the first Nigerian band officer to ascend the position of the Director of Music of the Nigerian Army. Moreover, he contributed in no small measure towards the establishment of the Nigerian Army School of Music, as well as in the music training of many of the prominent Nigerian military band officers that later came on the scene. The paper concluded that, in order to come out with the much-expected theory on the European-styled military music on African soil, research works should be carried out on more of the military composers of diverse nationalities in Africa.